THE DEVELOPMENT OF PURE-SYSTOLIC ALGORITHM FOR COMPUTING NUMBER-THEORETIC TRANSFORMS OF SIGNALS - Ekaterina Viktorovna Toporkova; Maksim Igorevich Kalmykov; Elena Pavlovna Stepanova; Dmitry Vladimirovich Yurdanov; Igor Anatolyevich Kalmykov (Современная наука и инновации)
The search for new ways to improve the efficiency of digital signal processing has led to the intensification of the deconveyor methods of calculations implemented on the basis of pure systolic matrices allows to increase the speed of the theoretical and numerical transformations of signals.